Clinical and mycological responses to fluconazole and fluconazole MIC in oropharyngeal candidiasis in HIV-infected patients. - Bussaratid, V; Tansupasawasdikul, S; Simpson, A; Pitisuttithum, P; Phonrat, B; Howe, P; White, N (2002)
INTRODUCTION: OPC is a common opportunistic infection in HIV-infected patients. Although some patients are asymptomatic, progression of the disease may occur leading to esophageal candidiasis. Fluconazole resistant candidiasis has been reported in several international studies. OBJECTIVES: This study aimed to test the MICs (minimal inhibitory concentrations) to fluconazole of Candida species isolated from mouthwash specimens of 54 HIV positive patients with oral candidiasis. Clinical and mycological responses to fluconazole were also assessed in 16 patients. MATERIAL AND METHOD: This was a prospective study. Mouthwash specimens were cultured on sabouraud dextrose agar twice. Candida species identification was performed and MICs for fluconazole were obtained using NCCLS guidelines. Clinical and mycological responses were assessed on day 14 and 42 in 16 patients who received a 14-day course of fluconazole. RESULTS: 48/54 patients (88.89%) were found to carry pure C. albicans. The other 6 patients (11.11%) had mixed Candida species on cultures. Among these 6 patients, 5 patients had mixed C. albicans and C. glabrata, and 1 patient had C. albicans and C. krusei. Fluconazole MICs of C. albicans, C. glabrata, and C. krusei ranged from 0.125-32 (median=0.250), 4-64 (median=2), and 8 g/L respectively. This study showed that the MICs to fluconazole of oropharyngeal Candida was a good predictor of the therapeutic responses.